Project Management And Coastal Structure Resilience: An Exploratory Study In Karawang Regency - Wuwuh Asrining Puri; M. Adik Rudianto; Rakhmad Wahyudi; Hafizh Fianto Putra (Yayasan Riset dan Pengembangan Intelektual, 2026)
Coastal protection structures such as breakwaters and groins are essential for mitigating shoreline erosion along Indonesia’s vulnerable coastlines, including the Karawang coast on the north coast of Java. This study explores the relationship between project management practices and the resilience of coastal protection structures through an exploratory case study of eight breakwater and groin projects in Karawang. Data were collected using structured surveys administered to project managers and technical personnel, complemented by field assessments of structural condition and functional performance. These indicators were combined into a Coastal Structure Resilience Index (CSRI), a composite measure of each structure’s physical integrity and functional effectiveness. Descriptive and regression analyses indicate a positive association between project management performance and structural resilience, with quality management appearing as the most prominent directional factor. Due to the limited sample size, the results should be considered exploratory rather than statistically conclusive. Nevertheless, the findings suggest that projects characterized by stronger quality control and schedule management tend to achieve better long-term structural conditions. The study highlights the potential importance of effective project management in coastal infrastructure resilience and recommends broader studies across multiple Indonesian coastal regions to support more robust conclusions.